Comparing charismatic leaders' communication styles a study of presidents Barack Obama and Donald Trump - McMahon, Tim P. 1954- (Routledge, 2025)
"In examining the presidencies of Barack Obama and Donald Trump, and by extension their communication styles, this book provides a foundation for understanding charismatic leadership and its potent effect on followers. The book identifies each leader's charismatic leadership attributes, focusing specifically on communication and impression management. It presents a qualitative collection of leader observations and outcomes based on publications and audio and video recordings. By examining two distinctly different leaders, each with evidence of effective, if controversial, outcomes, it shows a spectrum of approaches to mobilizing followers. This book is suited to students and readers interested in leadership studies, leadership communication, and persuasion"--
"Routledge Focus"--Cover. - Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on August 30, 2024)
Keywords: Obama, Barack -- Oratory; Trump, Donald -- 1946- -- Oratory; Charisma (Personality trait) -- Political aspects -- United States; Communication in politics -- United States; Rhetoric -- Political aspects -- United States; Charisme; Aspect politique; États-Unis; Communication politique; États-Unis; Discours politique; États-Unis; LANGUAGE ARTS & DISCIPLINES / Communication; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Public Relations; États-Unis; Politique et gouvernement; 2009-2017; États-Unis; Politique et gouvernement; 2017-2021; United States -- Politics and government -- 2009-2017; United States -- Politics and government -- 2017-2021